2012
DOI: 10.7314/apjcp.2012.13.2.621
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in Interleukin-2 and Risk of Lymphoma among Children in Korea

Abstract: To estimate the genetic susceptibility for childhood lymphoma, we conducted an association study for 23 cases and 148 controls. Total 1536 tag single nucleotide polymorphisms (SNPs) were selected in 138 candidate gene regions related to immune responses, apoptosis, the cell cycle, and DNA repair. Twelve SNPs were significantly associated with the risk of lymphoma (P trend <0.05) in six genes (IL1RN, IL2, IL12RB1, JAK3, TNFRSF13B, and XRCC3). The most significant association was seen for IL2 variant rs2069762 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Accumulated evidence has indicated that any abnormal expression or anergy caused by mutations of any component in Ca 2+ /NFAT signaling pathway could be closely related to the change of signal intensity or transmission, thus contributing to the pathogenesis or progression of diseases, especially the immune-related diseases373839404142. As far as our current findings were concerned, one of the positive results on SNP rs2720378 was also observed in one previous study conducted by Onouchi et al19.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Accumulated evidence has indicated that any abnormal expression or anergy caused by mutations of any component in Ca 2+ /NFAT signaling pathway could be closely related to the change of signal intensity or transmission, thus contributing to the pathogenesis or progression of diseases, especially the immune-related diseases373839404142. As far as our current findings were concerned, one of the positive results on SNP rs2720378 was also observed in one previous study conducted by Onouchi et al19.…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, SNP rs2069762, a single base change proximal to the IL-2 promoter region (−330A > C), was also predicted as affecting TFBS activity, where the C allele had a significantly higher score than the A allele. What's more, it has been proved that individuals homozygous for the C allele of rs2069762 produced over three times the amount of IL-2 than their AA and AC counterparts after stimulation with anti-CD3/CD2825, and then correlated with a series of inflammatory or immunological diseases, such as ulcerative colitis40, multiple sclerosis41, and childhood lymphoma42. Therefore, we considered that it was biologically plausible that SNP rs2069762 was also associated with increased KD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory response is regulated through a complex network of cytokines, cytokine receptors and downstream targets that synergistically regulate innate/humoral immune and inflammatory processes. Recent molecular and genetic epidemiology studies have demonstrated that chronic inflammation and susceptibilities in inflammatory-associated genes are related to the development of several cancers, including lymphoma, and gastric and prostate cancer [6,16,24-26]. However, to our knowledge, there are few published reports on the impact of variant cytokine-related genes in relation to prostate cancer among men of African Descent.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, inflammation-related genes may play a role in chronic antigenic stimulation, which is a key mechanism for lymphomagenesis. Whereas a number of case-control association studies have examined the role of genetic polymorphisms of inflammation-related genes in lymphoma risk (Rothman et al, 2006;Song et al, 2012). In recent studies, enough evidence has showed that the polymorphic variations of inflammation-related genes could overall be associated with the risk of NHL or some of its subtypes.…”
Section: Introductionmentioning
confidence: 99%